"Landscape" of energy burden: role of solid fuels in Central and Eastern European residential heating - Szép, Tekla; Pálvölgyi, Tamás; Kármán-Tamus, Éva (International Journal of Sustainable Energy Planning and Management, 2023)
Energy convergence, the decoupling of economic growth and energy use, and sustainable energy transition are all desirable objectives in the European Union. However, there are many contradictions and conflicts in the energy and climate policy that slow down the energy transition. In this paper, we focus on these barriers. A fuel-specific indicator is developed (share of household energy expenditure - SHEE) and used in the calculations. The main research objective is to measure the changes in the household energy mix in Central and Eastern Europe (CEE) and infer the degree of the energy transition in the household sector. For this purpose, Moore index and delinking factor are applied. The results shed light on the slowness of the just energy transition and confirm the presence of the dual fuel trap. The households in CEE have been stuck in the traditional biomass trap and beyond it, the natural gas consumption also contributes to higher exposure and vulnerability of households. We conclude that territorial differences and spatial characteristics of household energy use need more attention to achieve the energy and climate policy agenda of the European Union.